Choosing a response topography for individuals with autism during functional communication training: A critically appraised topic. Issue 1 (3rd April 2019) - Carnett, Amarie; Neely, Leslie; Hong, Ee Rea; Escobar, Julie
Abstract: A critically appraised topic (CAT) is one form of rapid review that can be particularly useful for informing practice. The purpose of this CAT was to examine the effects of mand preference on Functional Communication Training outcomes in individuals with autism spectrum disorder and to describe procedures used to assess preference for a mand topography. In addition to the methodology, the authors present and discuss the findings of this CAT. The authors propose an update to this CAT in September 2021.